2020
DOI: 10.3390/plants9050612
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones Control Root System Architecture and Tip Anatomy in Solanum lycopersicum L. Plants under P Starvation

Abstract: The hormones strigolactones accumulate in plant roots under phosphorus (P) shortage, inducing variations in plant phenotype. In this study, we aimed at understanding whether strigolactones control morphological and anatomical changes in tomato (Solanum lycopersicum L.) roots under varying P supply. Root traits were evaluated in wild-type seedlings grown in high vs. low P, with or without exogenous strigolactones, and in wild-type and strigolactone-depleted plants grown first under high vs. no P, and then under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 62 publications
(97 reference statements)
1
22
0
Order By: Relevance
“…The modification of resource distribution in favour of belowground biomass production over shoot growth negatively correlated with the plant P content (ρ = 0.867, p < .01) in both genotypes. This is a typical response to P starvation intended to increase soil exploration and P uptake by roots (Aziz et al, 2014;Niu et al, 2013;Ramaekers, Remans, Rao, Blair, & Vanderleyden, 2010); the fact that it was observed in both wild-type and SL-depleted plants confirms that the differences between these genotypes observed by Santoro et al (2020) under -P conditions were likely due to differences in root anatomy and topology rather than biomass allocation.…”
Section: Kinetics Of Dissolved Organic C and Organic Acid Exudationmentioning
confidence: 85%
See 1 more Smart Citation
“…The modification of resource distribution in favour of belowground biomass production over shoot growth negatively correlated with the plant P content (ρ = 0.867, p < .01) in both genotypes. This is a typical response to P starvation intended to increase soil exploration and P uptake by roots (Aziz et al, 2014;Niu et al, 2013;Ramaekers, Remans, Rao, Blair, & Vanderleyden, 2010); the fact that it was observed in both wild-type and SL-depleted plants confirms that the differences between these genotypes observed by Santoro et al (2020) under -P conditions were likely due to differences in root anatomy and topology rather than biomass allocation.…”
Section: Kinetics Of Dissolved Organic C and Organic Acid Exudationmentioning
confidence: 85%
“…T A B L E 3 Parameters of the mathematical functions fitted to cumulative proton (H + ), dissolved organic C (DOC) and organic acid anions data, as reported in Figures 6-8 The phenotype of the SL-depleted plants used in this study has been described in the past, limited to morphology and physiology under Preplete conditions (Visentin et al, 2020;Vogel et al, 2010) and to fine root morphology and tip anatomy under both P-replete and P-deplete conditions (Santoro et al, 2020). Our study extended their characterization under P starvation, and complemented it with data on the allocation of macroelements (C, N and P) and on the effect of exogenous SLs on PAE and PUtE.…”
Section: Kinetics Of Dissolved Organic C and Organic Acid Exudationmentioning
confidence: 99%
“…For example, as mentioned above, when roots produce and release SLs into the soil as they do especially under nutrient-limiting conditions, they promote the symbiosis with beneficial fungi [ 6 ] and thus, indirectly improve their own nutrition [ 7 ]. It is also suggested that SLs are important for direct acclimation responses and plant plasticity in response to nutrient availability, notably by inhibiting branching/tillering and shaping root architecture under low nutrients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Santoro et al [ 27 ] investigated the role of an emerging class of phytohormones, namely strigolactones (SL), on root anatomy and system architecture traits of wild-type and strigolactone-depleted tomato plants grown under different phosphorus (P) foraging conditions. Strigolactones are involved in root–rhizosphere interactions by promoting mycorrhiza symbiosis establishment under P limitation, and mediate the signaling networks in plants that crosstalk with those of other phytohormones during P perception and signal transduction [ 28 , 29 ].…”
Section: Highlights Of the Special Issuementioning
confidence: 99%